ジキケン アラシ カイシジ ノ VLF LF デンパ バースト - 恩藤, 忠典; オンドウ, タダノリ; 藪馬, 尚; ヤブウマ, ヒサシ; 大瀬, 正美; オオセ, マサミ; 西牟田, 一三; ニシムタ, イチゾウ; ONDOH, Tadanori; YABUUMA, Hisashi; OSE, Masami; NISHIMUTA, Ichizo (国立極地研究所, 1976)
P(論文) 南極昭和基地で観測したVLF放射狭帯域強度(5.0土0.2kHz, 12.0士0.5kHz, 50.0士1.0kHz),地磁気水平成分,リオメーター30MHz の同時記録データを用いて,磁気圏嵐の局所的開始に伴うVLF電波バーストの解析を行った.1973年の6ヵ月間に起こった59個の磁気圏嵐に伴って発生したVLF電波バーストを統計処理した結果,磁気圏嵐の局所的開始から5分間以内に,5kHz, 12kHz, 50kHz の各周波数において,広帯域な電波バーストが頻発していることが明らかになった.このVLF-LF電波バーストに伴うリオメーター30MHzの電離層吸収ぱ小さく,D層まで侵入するような数10keV以上の電子は,VLF-LF電波バーストの発生とあまり関係しないことを示している.磁気圏嵐の局所的開始が,オーロラのbreakupと一致していることからも,10keV以下のオーロラ電子からの広帯域なセレンコフ型放射が,VLF-LFバーストの発生機構と思われる.磁気圏嵐の成長期にはプラズマシートの薄化が起こり,磁気中性シートの西向き電場が強化され磁気圏尾部での内向きプラズマ対流が発達する.プラズマ対流の発達に伴い,プラズマシート内端近くで静電気的プラズマ不安定が発生し,プラズマシート電子はピッチ角拡散によって,磁力線に沿って極光帯へ降下する.このオーロラ電子からのセレンコフ型放射が,磁気圏嵐開始時の広帯域VLF-LF電波バーストを発生すると推測される.VLF放射,地磁気活動,極光現象,電子降下現象のcorrelation dataは,極光帯電離層,磁気圏尾部の物理的機構の解明に重要なもので,今後とも続行すべきものである. Observations of VLF hiss narrow-band intensities (5.0±0.2 kHz, 12.0±0.5 kHz, and 50.0±1.0 kHz), horizontal component (H) of the geomagnetic field, and the ionospheric absorption of cosmic radio noises of 30 MHz have been carried out at Syowa Station, Antarctica, since May, 1972. Characteristics of VLF-LF radio emissions associated with 59 magnetospheric substorms which occurred for six months in 1973 have been statistically analyzed by using the above correlation data. Wide-band VLF-LF radio bursts are often found at all channels of 5 kHz, 12 kHz, and 50 kHz within 5 minutes of local onsets of magnetospheric substorms. Small absorption (less than about 0.5 dB) of the cosmic radio noises at 30 MHz suggests that precipitations of energetic electrons above 10 keV into the auroral-zone ionosphere have little relation with the generation of VLF-LF radio bursts. The cerenkov-type wide-band emissions from auroral electrons below lOkeV may generate VLF-LF radio bursts, since the auroral breakup occurs simultaneously with the local onset of magnetospheric substorm. In the growth phase of the magnetospheric substorm, intensification of the westward electric field in the neutral sheet associated with thinning of the plasma sheet causes the inward plasma flow in the magnetotail. The electrostatic plasma ...